Reconstruction and Development of Tourism Potentials in the Fishermen’s District Village of Medan Belawan - Wahyuni Zahrah; Ridho Adjie Pangestu (Talenta Publisher, 2018)
Belawan Fishermen Village is a Fisherman Village on the edge of Medan City. The fisherman is the biggest livelihood in this village. A Spatial also has a lot of activities / local wisdom as well as traditions such as traditional rowing racing, drying salted fish and catching fish. The problems of the Villages are from poverty, lack of green open space, dirty and smelly environments, waste everywhere, improper laying of buildings, and inadequate water supply. The structures of buildings and building materials in these villages are also included in the inappropriate category. This design aims to make this village as a tourist village, comfortable to live and visited by tourists, and make a friendly village face with the surrounding environment, and can improve the lives of citizens. Also, it can improve the lives of citizens. Realizing the theme of tourism by taking the potential and cultural character and local wisdom which is then implemented in the form of tourism. There are several aspects of design in this design include the following:In the aspect of this village activity, there are 2 activities that are the daily activities of citizens and tourism activities.In the aspect of this village, the site has two accesses, on land in the form of decks that are 2m wide as well as ocean circulation that is connected directly to the pier deck of residents' homes.In the aspect of the building, the building in this village uses a structure that is resistant to seawater. In addition to being able to withstand vertical and lateral shocks and buffers that with PVC pipe material filled with cement. Utilities make a biofiltration system that treats waste before entering the sea considering the area of the settlement is a conservation area.